2020
DOI: 10.1111/tri.13687
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with 17β‐estradiol protects donor heart against brain death effects in female rat

Abstract: The viability of donor organs is reduced by hemodynamic and immunologic alterations caused by brain death (BD). Female rats show higher heart inflammation associated with the reduction in female sex hormones after BD. This study investigated the effect of 17b-estradiol (E2) on BD-induced cardiac damage in female rats. Groups of female Wistar rats were assigned: Sham-operation (Sham), brain death (BD), treatment with E2 (50 lg/ml, 2 ml/h) 3 h after BD (E2-T3), or immediately after BD confirmation (E2-T0). White… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…Previous studies have shown a higher inflammatory female condition in relation to male donor, which was correlated with acute estradiol reduction following BD (5)(6)(7). In BD female rats, treatment with E2 efficiently reduced heart and lung injury, modulated inflammatory cell infiltration, enhanced release of chemokines, and suppressed cardiomyocyte apoptosis (8,9). Female sex hormone concentrations acute reduction after BD may occur probably due to interruption of the hypothalamic-pituitary-ovary axis and affects the control of several nonreproductive tissues including the immune system (5).…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Previous studies have shown a higher inflammatory female condition in relation to male donor, which was correlated with acute estradiol reduction following BD (5)(6)(7). In BD female rats, treatment with E2 efficiently reduced heart and lung injury, modulated inflammatory cell infiltration, enhanced release of chemokines, and suppressed cardiomyocyte apoptosis (8,9). Female sex hormone concentrations acute reduction after BD may occur probably due to interruption of the hypothalamic-pituitary-ovary axis and affects the control of several nonreproductive tissues including the immune system (5).…”
Section: Discussionmentioning
confidence: 73%
“…The E2 treatment was based on previous studies (8,9), using the same model of BD, in which both treated groups presented similar increases in serum estradiol levels after the end of E2 infusion compared to the BD group (BD =68.2±8, E2-T0 =1,713.5±44.7, E2-T3 =1,717.9±29.2 pg/mL; P<0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations